Development of fibre-reinforced composite disk for computer-aided design-computer-aided manufacturing milled posts; Experimental composite disk using e-glass fibre in different fibre direction - Warin Prachasujit; Somchai Urapepon (Wolters Kluwer Medknow Publications, 2021)
Aims: To evaluate the flexural properties of computer-aided design-computer-aided manufacturing (CAD-CAM) milled posts fabricated from the experimental fibre-reinforced composite disks in different fibre direction, and to compare the flexural properties of the CAD-CAM milled posts to those of commercial prefabricated posts, RelyX and FRC PostecPlus. Settings and Design: In vitro comparative study. Materials and Methods: E-glass fibre was used to fabricate the CAD-CAM composite disks. The fibres were prepared in unidirectional and multidirectional arrangements into the epoxy resin, at 70% by weight. The disk was milled by the Cerec InLab CAD-CAM system to fabricate a post. Ten posts for each type of disk were prepared. Two types of commercial fibre posts, RelyX fibre post, and FRC PostecPlus were used as control. The three-point bending test was performed. Statistical Analysis Used: The data were analysed using one-way ANOVA and Game-Howell post-hoc test. Results: The results indicated that both commercial fibre posts had the highest flexural strength and flexural modulus. The unidirectional experimental post yielded significantly lower values in both flexural strengths (739.1 ± 24.1 MPa) and flexural modulus (21.0 ± 3.5 GPa) compared to the control posts, while the multidirectional experimental posts had extremely low flexural strength and flexural modulus. Conclusions: The direction of the fibres significantly influenced the mechanical properties of the posts. The experimental unidirectional fibre-reinforced composite disk showed the potential to be used as a CAD-CAM disk for post and core fabrication.